Early life antibiotics and childhood gastrointestinal disorders: a systematic review. Issue 1 (3rd March 2021) - Kamphorst, Kim; Van Daele, Emmy; Vlieger, Arine M; Daams, Joost G; Knol, Jan; van Elburg, Ruurd M
Abstract : Background: In adults, there is increasing evidence for an association between antibiotic use and gastrointestinal (GI) disorders but in children, the evidence is scarce. Objective: Assess the association between exposure to antibiotics in the first 2 years of life in term born children and the presence of chronic GI disorders later in childhood. Design: For this systematic review the MEDLINE, Embase, WHO trial register and Web of Science were systematically searched from inception to 8 June 2020. Title and abstract screening (n=12 219), full-text screening (n=132) as well as the quality assessment with the Newcastle-Ottawa Scale were independently performed by two researchers. Main outcome measures: The association between antibiotics and inflammatory bowel disease (IBD) (n=6), eosinophilic oesophagitis (EoE) (n=5), coeliac disease (CeD) (n=6), infantile colics (n=3), functional constipation (n=2), recurrent abdominal pain, regurgitation, functional diarrhoea and infant dyschezia were examined. Results: Twenty-two studies were included, 11 cohort and 11 case–control studies. A best evidence synthesis showed strong evidence for an association between antibiotic exposure in the first 2 years of life and the presence of IBD, and CeD during childhood. Moderate evidence was found for an association with EoE and no association with functional constipation in the first year of life. There was insufficient evidence for the other studied disorders. Conclusions: The use of antibiotics in early life may increase the risk of GI disorders later in life. Further studies are necessary to unravel the underlying mechanisms and determine potential preventive measures. Meanwhile judicious use of antibiotics in early childhood is highly warranted. PROSPERO registration number: PROSPERO CRD42019132631.